Changes in physical qualities in junior beach volleyball athletes transitioning to the world tour - Jones, D. (Journal of Australian Strength and Conditioning, 2020)
The purpose of this case study was to track the development of physical qualities in athletes that have transitioned from junior to senior international beach volleyball. Four male subjects (age = 19.5 +/- 1.0 years, height = 199 +/- 3.6cm, weight = 88 +/- 7.1kg) participated in this two-year longitudinal study. During the two-year investigation period all athletes debuted on the Federation of International Volleyball World Tour at a minimum of a 3-star level. Pre and posttest values for spike jump, block jump, countermovement jump, 10 m sprint, modified 505, repeated sprint ability, anthropometry and maximal strength of bench press, bench pull, back squat and power clean were recorded. Jumping variables including spike jump (6.5cm, 8.9%), block jump (6.3cm, 10.5%) and CMJ height (4.6cm, 9.4%) showed large improvements. A decrease in sum of 8 skinfolds (5.5mm, 8.4%) was also observed. Maximal strength levels, in particular lower body also improved across the investigation period with moderate and large improvements in power clean (15kg, 19.0%) and back squat predicted 1RM (21.5kg, 20.0%). Linear sprint change of direction speed and repeated sprint ability did not show significant improvement across the study period. To progress from junior to senior international beach volleyball representation, the development of spike, block and CMJ ability is necessary. Optimisation of body composition and improving lower body maximal strength are key qualities that support the improvement of jumping ability. Upper body strength, linear and change of direction speed, and repeated sprint ability may have a smaller role in determining a successful transition to senior beach volleyball.